Consumer Perceptions of Peanuts and Peanut Allergy: The EuroPrevall Results of Focus Groups in Poland - Anna Prusak; Małgorzata Schlegel-Zawadzka (Public Health, 2017)
Background: Food allergies represent a growing public health concern worldwide. For many people, peanut is a considered one of the basic foods, while for food industry, groundnuts are the cheapest substitute for other nuts. They are added to many goods. The aim of the study is to portray the “peanut culture” in Poland, by reporting perceptions of an ordinary consumer as regards peanuts, peanut products and peanut allergies. The study tries to explore the role of peanuts and peanut products in diet and life of Polish consumers, as well as their awareness about peanut allergy and restrictions on peanut consumption.Methods: Three focus groups sessions with consumers were carried out: C1 – 10 participants (part-time university students, recruited during their courses. It is important to note, however, that part-time studies in Poland are held during the weekends and consist primarily of people who work), C2 – 12 participants (participants were recruited through the advertisement in lo-cal/regional supermarkets) and C3 – 10 participants (a group of 12 people were recruited via regional newspaper (Dziennik Polski) in the vacancy announcement). The protocol was pre-pared as part of the EuroPrevall project, Work Package 2.3. All sessions lasted between 45 and 60 minutes. Each session was type-recorded and transcribed. Each transcript was coded using Atlas.ti (5.0) software for qualitative analysis.Results: The current paper focuses at themes related directly to peanut consumption habits and awareness/perception of peanut allergy, specifically: personal preferences for peanuts; types, forms and place of peanut consumption; tradition of peanut consumption and its change over years; health issues and awareness of peanut allergy; early exposure to peanuts. Consumers in Poland can be divided into those who like peanuts and eat them, those who do not like peanuts for various reasons (i.e. lack of habit to eat peanuts) and never eat them and those who eat pea-nuts occasionally, i.e. in pubs, bars, at parties, but do not usually buy them. The latter category involves most participants. Conclusion: The results described in this paper indicate that more information is needed as regards food and peanut allergy. Peanuts in hidden form require special attention and clearer labelling, which is important especially for children suffering from peanut allergy. Authorities need to publish guidelines as regards peanut consumption during pregnancy and breastfeeding, or at least doctors should inform patients about the risk of developing peanut allergy as a result of early exposure.